From Eastern Bloc to European Union : comparative processes of transformation since 1990 - Heydemann, Günther; Vodička, Karel (2017)
"More than 25 years after the fall of the Soviet Union, European integration remains a work in progress, especially in those Eastern European nations most dramatically reshaped by democratization and economic liberalization. This volume assembles detailed, empirically grounded studies of eleven states–Estonia, Latvia, Lithuania, Poland, the Czech Republic, Slovakia, Hungary, Romania, Bulgaria, Slovenia, and the former East Germany–that went on to join the European Union. Each chapter analyzes the political, economic, and social transformations that have taken place in these nations, using a comparative approach to identify structural similarities and assess outcomes relative to one another as well as the rest of the EU."–Provided by publisher